Implementation and preliminary evaluation of a structured stepwise training program for laparoscopic partial nephrectomy: a single-center pilot study - Zhao, Yi; Wang, Wenda; Zuo, Yuzhi; Ji, Zhigang; Wu, Xingcheng (Frontiers in Medicine, 2026)
ObjectiveThe objective of this pilot study was to assess the effectiveness of a (multimodal) structured training program, using (stepwise) stages of experience, to improve laparoscopic partial nephrectomy (LPN) skills among two groups of urology (URO) trainees. Key metrics of performance (KPIs) were recorded and compared between the groups.ResultsTime to being ready for the first supervised laparoscopic partial nephrectomy (LPN) for the structured training group was significantly less than the control group (5.65 months vs. 6.80 months; p < 0.001), as was duration for performing the first LPN (88.15 min vs. 101.35 min; p < 0.001). The structured training group received higher faculty performance scores than the control group (8.30 vs. 7.15, p < 0.001).ConclusionThe development of a standardized structured training curriculum resulted in enhanced skill acquisition and an improved initial operative performance compared to a control group. However, while these results are encouraging, they are preliminary and limited by the lack of an equivalent concurrently documented control. Therefore, these results should be interpreted as evidence demonstrating the benefit of a systematic approach to surgical education and require further investigation through multicenter studies.